Extraction and activity of chemical constituents from Houttuynia cordata Thunb by ultrasonic method - Song, Huwei; Shen, Tong; Wu, Jincheng; Lin, Shoukai; Diao, Enjie; Li, Zhengpeng; Qian, Shiquan (Cellular and Molecular Biology, 2022)
Polyphenols and flavonoids are phytochemicals that have essential roles in human nutrition. In this regard, the contents of polyphenols and flavonoids in Houttuynia cordata Thunb and their antioxidant activities were evaluated in the current study. Two Houttuynia cordata materials with the same chromosome number and chemical type were used to comprehensively assess the contents of total phenols and flavonoids in different parts of H. cordata. These chemical components were extracted by the ultrasonic method. The results showed that the total phenols and antioxidant capacity of different parts of H. cordata were significantly different. The content of polyphenols in roots and stems was low, the antioxidant capacity was weak, the total phenols in flowers and leaves were high, and the antioxidant capacity was strong. Therefore, different parts of H. cordata had different pharmacological and food effects. The whole herb can be used as Chinese herbal medicine, and its young leaves and roots can be used as vegetables. Flavonoids are the main phenolic components, and total phenols are the main components of antioxidant activity. It can explain a very significant positive correlation between total phenols and flavonoids. Therefore, in the further breeding work of H. cordata, the procedure can be simplified by determining one of the above indexes to predict the varieties with high total phenolic and antioxidant activity.